2006
DOI: 10.1300/j020v24n01_04
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Supports, Spirituality, Religiousness, Life Meaning and Affiliation with 12-Step Fellowships in Quality of Life Satisfaction Among Individuals in Recovery from Alcohol and Drug Problems

Abstract: SUMMARYMany recovering substance users report quitting drugs because they wanted a better life. The road of recovery is the path to a better life but a challenging and stressful path for most. There has been little research among recovering persons in spite of the numbers involved, and most research has focused on substance use outcomes. This study examines stress and quality of life as a function of time in recovery, and uses structural equation modeling to test the hypothesis that social supports, spirituali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
175
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(197 citation statements)
references
References 142 publications
(141 reference statements)
14
175
0
8
Order By: Relevance
“…It means that in self-help groups in Poland spiritual experiences play an important role in recovery. It is consistent with results of research in a sample of AA where spirituality positively correlated with quality of life indicators [51][52][53]. Hope seems to be relevant for successful therapy as a key factor for implementing some changes in functionality [54][55][56].…”
Section: Discussionsupporting
confidence: 87%
“…It means that in self-help groups in Poland spiritual experiences play an important role in recovery. It is consistent with results of research in a sample of AA where spirituality positively correlated with quality of life indicators [51][52][53]. Hope seems to be relevant for successful therapy as a key factor for implementing some changes in functionality [54][55][56].…”
Section: Discussionsupporting
confidence: 87%
“…Recovery capital includes variables such as spirituality, religion, life meaning, and 12-step affiliation (Laudet, Morgen, & White, 2006) which are thought to reflect an individual's embeddedness in their social and cultural life (Granfield & Cloud, 2001;Laudet, et al, 2006). Enhancing components of recovery capital may buffer the effects of stress (Laudet, et al, 2006;Laudet & White, 2008) and lead to improved mental health.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Studies have identified social support as a key protective factor in addiction [68][69][70]. Fuelling the 'globalization of addiction' [60] is the breakdown of family and community in a world of rampant consumerism and individualistic interests.…”
Section: Discussionmentioning
confidence: 99%